Electrophilic derivatives antagonise pheromone attraction in Cydia pomonella. Issue 11 (3rd April 2013) - Sans, Albert; Gago, Rafael; Mingot, Ares; García, Wanda; Bosch, Dolors; Coll, Josep; Rosell, Gloria; Bosch, M Pilar; Riba, Magí; Guerrero, Angel
Abstract BACKGROUND Pheromone antagonists are good disruptants of the pheromone communication in insects and, as such, have been used in mating disruption experiments. In this study, new non‐fluorinated electrophilic keto derivatives structurally related to the pheromone of Cydia pomonella (codlemone) have been synthesised and tested as putative pheromone antagonists. RESULTS Codlemone (1) was prepared in excellent stereoselectivity in a new, iterative approach involving two Horner–Wadsworth–Emmons reactions. Methyl ketone (2), keto ester (3) and diketone (4) were obtained from codlemone in straightforward approaches in good overall yields and excellent stereochemical purity (≥98% E, E). In electrophysiology, only compound 2 displayed inhibition of the antennal response to the pheromone after presaturation of the antennal receptors. Compounds 2 to 4 did not inhibit the pheromone‐degrading enzyme responsible for codlemone metabolism, but mixtures of ketone 2 and diketone 4 with codlemone elicited erratic flights on males in a wind tunnel. In the field, blends of either compound (2 or 4) with the pheromone caught significantly fewer males than codlemone alone. CONCLUSION Codlemone and the potential antagonists 2 to 4 have been synthesised in good yields and excellent stereoselectivity. These chemicals behave as pheromone antagonists of the codling moth both in the laboratory and in the field. © 2013 Society of Chemical Industry